Static tensile test of metal alloys - Goh, Xue Zi (Nanyang Technological University, 2020)
This Final Year Report reviews the project B172 on Static Tensile Test of Metal Alloys. The project is about studying and experimenting of the metal alloy, Aluminium 6061-T6. Through performing Static Tensile test, the material desired mechanical properties can be obtained. The objective is to obtain the stress-strain relation of metals by the international standards of tensile testing. The author read and understand the standard, ASTM E8/E8M-15a, and literature review regarding static tensile test, perform and determined a suitable method for the project. The fabrication of the test specimen is in accordance to the ASTM standard. Unlike the project conducted by the previous student, the specimen with longitudinal and transverse grain direction is fabricated with the use of milling machine instead of EDM wire cutting. The experiment is carried out to obtain mechanical properties of longitudinal and transverse direction specimen and find out how different grain structure would influence the mechanical properties of the material. The test is conducted, and the stress-strain curves will be plotted with the data collected. The results will be analysed and compared to reach a conclusion and would be recorded in the report and serve as an addition to the database for future student references and allow them to conclude a trend displayed by the testing. The project will also focus on improving the experiment to obtain more accurate and reliable results. This report will be beneficial for future reference on the static tensile test for Aluminium 6061-T6. Future student will be able to use a more suitable machine method to fabricate their specimens. In addition, recommendations for static tensile test will be discussed for future students to make improvement on the experiment.